Physical impairments in individuals with Long COVID - Imane Salmam; Imane Salmam; Kadija Perreault; Kadija Perreault; Krista L. Best; Krista L. Best; Imane Zahouani; Gilles Drouin; Jean Tittley; François Desmeules; François Desmeules; Alexandre Campeau-Lecours; et al. (Frontiers in Sports and Active Living)
ObjectiveThe primary objective was to compare the physical capacities of individuals with Long COVID [Long COVID group (LCG)] to those who had COVID-19 but did not develop persistent symptoms [short COVID group (SCG)], and to individuals without a history of COVID-19 [control group (CG)]. The secondary objectives were to provide a comprehensive profile of sociodemographic and COVID-19 history of individuals with Long COVID, considering factors such as sex, gender, hospitalization, time since onset, and comorbidities, and b) identify self-reported and objective clinical measures explaining health-related quality of life (HRQoL) in individuals with Long COVID.MethodsA total of 120 adults were included in each of the groups. Participants completed self-reported assessments covering HRQoL, comorbidities, pain, sleep, and fatigue. Physical assessments included handgrip strength (HGS), Short Physical Performance Battery (SPPB), 6-minute-walk-test (6MWT), perceived exertion during the 6MWT (Modified-Borg Scale), and daily step count during a 7-day period.ResultsMean age (mean [SD]) for LCG, SCG, and CG was 44.2 [11.2], 42.1 [16.4], and 46[15.9], respectively. LCG showed significantly higher pain, comorbidities, and fatigue, along with lower HRQoL and sleep quality compared to the other groups. HGS, SPPB, and 6MWT performance were also significantly lower in LCG, while perceived exertion during 6MWT was higher. Finally, the number of steps per day was significantly lower in LCG. Higher prevalence of obesity and comorbidities were identified among those hospitalized after COVID-19. Fatigue, pain, comorbidities, and Step count were the variables explaining HRQoL for LCG (R2: 0.58; F = 35.9).ConclusionLong COVID individuals, on average 329 [146] days post-infection, experience enduring physical and health-related challenges, with significant implications for their overall well-being.